PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK SADAR WISATA (POKDARWIS) SUKOMAKMUR DALAM PENGEMBANGAN DESA WISATA KANDRI KOTA SEMARANG - Artanti Nirwana, Nurulita; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
Community empowerment is a process aimed at enhancing the abilities and strengths of a community, enabling individuals to become self-reliant in determining their own future. However, community empowerment through the Sukomakmur Tourism Awareness Group (Pokdarwis Sukomakmur) has been hindered by insufficient levels of training and guidance. The low educational level of its members has resulted in a lack of knowledge regarding tourism village management, and the leadership has been unresponsive to the needs of its members. This research aims to analyze community empowerment efforts through the Sukomakmur Tourism Awareness Group in the development of the Kandri Tourism Village in Semarang City, as well as to identify the supporting and inhibiting factors involved. The research utilizes Mardikanto’s community empowerment theory and Ambar T. Sulistyani’s stages of community empowerment. The method employed is qualitative, with descriptive analysis. Data collection was conducted through interviews, observations, and documentation. Sampling techniques included purposive sampling and snowball sampling. The research findings indicate that, among the three indicators of community empowerment stages, the capability transformation stage in Pokdarwis Sukomakmur is particularly affected by the low educational level of its members, limited human resources, and poor communication due to unresponsive leadership. The intellectual capability stage is also not yet optimal. Additionally, benchmarking studies with other tourism villages have not been effective, leading to a lack of understanding in managing the local tourism village. Inhibiting factors include limitations in human resources and communication. The recommendations from this research are that community empowerment efforts through Pokdarwis Sukomakmur should focus on improving the training and guidance provided to its members through targeted training programs, enhancing internal management and leadership within Pokdarwis Sukomakmur, and fostering better communication between the members and leadership by being more open to ideas and feedback.